Classification of elite cassava varieties (Manihot esculenta Crantz) cultivated in Benin Republic using farmers’ knowledge, morphological traits and simple sequence repeat (SSR) markers - Agre, A.P.; Bhattacharjee, Ranjana; Rabbi, Ismail Y.; Alaba, O.A.; Unachukwu, N.N.; Ayenan, M.A.T.; Loko, Y.L.; Bauchet, Guillaume J.; Dansi, A. (2017)
Cassava (Manihot esculenta Crantz) is an important food security crop or resource for poor rural communities particularly in Africa. The crop’s ability to produce high yields even under poor conditions and storability of its roots underground for longer periods or until needed makes it a model ‘food security crop’. In Benin Republic, cassava has been recognized as one of the major crop contributing towards dynamic value chains generating incomes for small-holder farmers. The crop is grown all over the country, however, the increased production are mainly recorded from far south and central parts of the country. Genetic improvement of cassava in Benin Republic is limited because of poor knowledge of genetic diversity present within the country. The main objective of this study was to assess the genetic diversity and relationships among elite cassava varieties collected from different regions of Benin using fluorescently labelled simple sequence repeat (SSR) markers and to compare the results with farmer’s knowledge and morphological traits. A total of 96 cultivars collected from major cassava growing areas such as Southern and Central Benin were classified into 24 different groups using farmers’ knowledge, while classification based on 18 morphological traits resulted in five groups. In total, sixteen SSR markers were tested for molecular analysis of the ninety-six cassava varieties. Among the sixteen, twelve SSR markers gave good banding pattern and were used to genotype the varieties. An average of 3.58 and 0.47 for number of alleles and polymorphism information content respectively was observed. The observed heterozygosity (Ho) ranged from 0.23 to 1.0 with an average of 0.66 indicating moderate level of diversity among the cultivars. Based on the proportion of shared alleles and hierarchical clustering, the 96 elite cassava varieties were classified as 74 unique varieties. Principal component analysis and analysis of molecular variance revealed no significant variation between the regions thus, explaining regular exchange of planting materials among cassava farmers across various regions. The moderate level of genetic diversity in famer’s field, revealed in the present study, is a good indication of the need for broadening the genetic base of cassava in Benin Republic and establishing a formal breeding program in the country.